(untitled) (مجلة أبحاث قانونية, 2023)
The sixth item of Article Two of Law No. 88 of 1971 regarding the administrative judicial circuits stipulates that these circuits are competent with cases related to nationality. The researcher tried to answer whether the administrative judicial circuits are competent with the original case of nationality as one of these cases or not? The research aimed to indicate the extent of the competence of the administrative judicial circuits in the original case of nationality. The researcher followed the descriptive approach in answering the question posed, and he concluded that the administrative judicial circuits have exclusive jurisdiction to adjudicate the original case of nationality like other nationalitycases. Hence, the person concerned may file a case before the administrative judicial circuits to recognize or deny the nationalityfor him, without there being a previous administrative decision related to nationality or a case filed before the court.